Comparative de novo transcriptomics and untargeted metabolomic analyses elucidate complicated mechanisms regulating celery (Apium graveolens L.) responses to selenium stimuli. - Chenghao Zhang; Baoyu Xu; Cheng-Ri Zhao; Junwei Sun; Qixian Lai; Chenliang Yu (PLoS ONE)
Presently, concern regarding the effects of selenium (Se) on the environment and organisms worldwide is increasing. Too much Se in the soil is harmful to plants. In this study, Illumina RNA sequencing and the untargeted metabolome of control and Se-treated celery seedlings were analyzed. In total, 297,911,046 clean reads were obtained and assembled into 150,218 transcripts (50,876 unigenes). A total of 36,287 unigenes were annotated using different databases. Additionally, 8,907 differentially expressed genes, including 5,319 up- and 3,588 downregulated genes, were identified between mock and Se-treated plants. "Phenylpropanoid biosynthesis" was the most enriched KEGG pathway. A total of 24 sulfur and selenocompound metabolic unigenes were differentially expressed. Furthermore, 1,774 metabolites and 237 significant differentially accumulated metabolites were identified using the untargeted metabolomic approach. We conducted correlation analyses of enriched KEGG pathways of differentially expressed genes and accumulated metabolites. Our findings suggested that candidate genes and metabolites involved in important biological pathways may regulate Se tolerance in celery. The results increase our understanding of the molecular mechanism responsible for celery's adaptation to Se stress.